PAMALI AS A REPRESENTATION OF MYSTICAL LOGIC IN GEN Z - Rachma, Awlia Dwi; Hasibuan, Rasya Nur Rasyida (Emerald: Journal of Economics and Social Sciences, 2024)
This study is trying to explore how gen z views Pamali as a representation of mystical logic. Based on Tan Malaka's theory regarding mystical logic, research was carried out to see whether gen z considers Pamali to be a representation of mystical logic. Simply because it contains elements of obscurity and occultism that cannot be empirically proven. The research was conducted using a qualitative research method using open and closed questionnaires to understand the thought of the 30 Gen Z selected from the sample. The results show that gen z thinks Pamali is a representation of mystical logic.